Rekonstruksi Kebijakan Hukum Ekonomi Syariah Berbasis Maqashid dan Maslahah di Era Digital - Ifatul Muzarkosah; Mochamad Sumpena (STAI Al Musaddadiyah Garut, 2026)
This study examines the legal challenges facing the Islamic economy in responding to the rapid, complex development of the digital economy. This study departs from the gap between the normative approach of maqashid al-sharia and the need for more operational policies in dealing with digital financial services, digital assets, and algorithm-based systems. Previous research generally still places maqashid al-sharia as an ethical foundation, but has not developed an applicative approach in the formulation of inclusive digital economy policies. This research uses a normative qualitative method with an approach to ushul fiqh and public policy through the analysis of classical literature, contemporary studies, and regulatory documents. The results of the study show that the maslahah-based approach is more adaptive and implementable in formulating Sharia economic law policies that are responsive to technological developments. This approach emphasizes distributive justice, expanded economic access, and consumer protection as the basis of inclusive and contextual digital economy policies. Keywords: Islamic Economic Law, Maqashid al-Syariah, Maslahah, Digital Economy.